2015
DOI: 10.1038/srep17361
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of co-denitrification in grazed grassland

Abstract: Pasture-based livestock systems are often associated with losses of reactive forms of nitrogen (N) to the environment. Research has focused on losses to air and water due to the health, economic and environmental impacts of reactive N. Di-nitrogen (N2) emissions are still poorly characterized, both in terms of the processes involved and their magnitude, due to financial and methodological constraints. Relatively few studies have focused on quantifying N2 losses in vivo and fewer still have examined the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 60 publications
5
27
4
Order By: Relevance
“…Codenitrification can occur in both fungi (e.g., Fusarium oxysporum) and bacteria (e.g., Streptomyces antibioticus) (37,47,48). This process with N 2 formation has previously been found in grassland and agricultural soils (47,49,50). The present study also demonstrated that codenitrification with N 2 formation coexisted with anammox and denitrification in N removal for forest soils under anaerobic conditions.…”
Section: Figsupporting
confidence: 80%
See 1 more Smart Citation
“…Codenitrification can occur in both fungi (e.g., Fusarium oxysporum) and bacteria (e.g., Streptomyces antibioticus) (37,47,48). This process with N 2 formation has previously been found in grassland and agricultural soils (47,49,50). The present study also demonstrated that codenitrification with N 2 formation coexisted with anammox and denitrification in N removal for forest soils under anaerobic conditions.…”
Section: Figsupporting
confidence: 80%
“…Our results for the soil from the mixed forest showed that codenitrification accounted for 2% to 12% of the total N 2 production ( Table 2). These results were much lower than in previous studies for two pasture soils (92% and 97%, respectively [49,50]) where the N 2 emission from codenitrification, including the part from anammox, was the dominant loss pathway. In addition, based on the original results from Long et al (47) and our equations as given above, the contribution of codenitrification was recalculated to be 0 to 68% of the total N 2 production for the six agricultural soils in the United States (see Table S2 in the supplemental material), assuming that 29 N 2 production with 15 NH 4 ϩ addition was from anammox.…”
Section: Figcontrasting
confidence: 75%
“…These data may be subject to artefacts if antibiotics repress NO 2 − oxidation, leading to NO 2 − accumulation and potential abiotic formation of N 2 and/or N 2 O. Our report also calls into question if codenitrification alone accounts for N 2 and N 2 O emissions following high doses of N as urea (approximately 9 mmol g −1 soil)13 and/or NO 2 − (166 mmol L −1 )10. If abiotic, hybrid N 2 is formed under these conditions, our understanding of soil fungal codenitrification and N trace gas emissions would need to be re-examined.…”
Section: Resultsmentioning
confidence: 80%
“…Codenitrification occurs when individual atoms of the N 2 O or N 2 molecules are derived from two distinct N sources910, resulting in hybrid N 2 8. Formation of hybrid N 2 is widely reported as evidence of anammox11 or codenitrification121314. Previously, isotope pairing experiments revealed chemodenitrification1516 and denitrification by the fungi Bipolaris sorokiniana used NO 2 − as the sole source for N 2 O formation16.…”
mentioning
confidence: 99%
“…1). Laughlin and Stevens (2002) confirmed the importance of co-denitrification for N 2 production, a process that may comprise 25 % of the total N balance in pastures (Selbie et al, 2015). Müller et al (2014) found that, for the same grassland soil as used in this study, co-denitrification contributed 17.6 % of the total N 2 O production.…”
Section: Introductionsupporting
confidence: 73%